Biological clock dysfunction exacerbates contact hypersensitivity in mice. (2nd November 2012) - Takita, E.; Yokota, S.; Tahara, Y.; Hirao, A.; Aoki, N.; Nakamura, Y.; Nakao, A.; Shibata, S.
Summary Background Immediate‐type skin allergic reactions, such as passive cutaneous anaphylactic reaction, are associated with circadian rhythm, but the role of circadian mechanisms on delayed‐type skin allergic reactions, such as contact hypersensitivity (CHS), remains uncertain. In mice, CHS, a T‐cell‐mediated immune response, is a classic model of human allergic contact dermatitis. Objectives We investigated whether biological clock dysfunction affects CHS pathogenesis in CLOCK mutant mice compared with wild‐type (WT) mice. Methods Mice were treated with 2, 4, 6‐trinitro‐1‐chlorobenzene (TNCB) on the abdominal skin on day 0 (sensitization) and then treated with TNCB on the ears on day 5 (challenge). Results We found that biological clock dysfunction resulted in severe inflammation. Ear swelling, serum immunoglobulin E level and mast cell number were significantly increased in CLOCK mutant mice compared with WT mice. These results provide evidence that CLOCK mutation promotes the T‐helper type 2 immune response and exacerbates CHS. Corticosterone has a protective effect on CHS. The serum corticosterone level lost rhythmicity and showed a decreased daily level in CLOCK mutant mice compared with WT mice, supporting the exacerbating effect of CLOCK mutation on CHS. Adrenalectomy markedly worsened TNCB‐induced CHS in WT mice but not in CLOCK mutant mice. In addition, dramatic dexamethasone‐induced protection of CHS was observed in CLOCK mutant mice compared with WT mice. Conclusions The present results suggest that circadian rhythm might be an important factor in the regulation of CHS via corticosterone rhythmicity and/or level.